Improving Customer Service and Satisfaction in Indonesian Digital Banks with AI-Powered Chatbots - Paulina Rosna Dewi Redjo; Diah Wuriah Ningsih; Tural Latif Gojayev (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
The integration of Artificial Intelligence (AI) chatbots into customer service operations within digital banks has become a transformative trend in the banking sector, particularly in Indonesia. This study examines the effectiveness of AI chatbots in improving both operational efficiency and customer satisfaction in three selected Indonesian digital banks. The research focuses on evaluating the impact of AI chatbots in reducing response times, handling high volumes of customer inquiries, and improving service availability. The study also delves into customer feedback, measuring satisfaction with the ease of use, personalization, and responsiveness of the AI systems. The results demonstrate that AI chatbots significantly enhance customer service efficiency by reducing wait times and automating routine inquiries, which reduces the need for human intervention. Additionally, customers reported high satisfaction with the round-the-clock availability of AI chatbots and the personalized financial advice provided. However, despite these benefits, challenges related to data security, chatbot accuracy, and customer adaptation to automated systems remain prevalent. Data privacy concerns and issues regarding the chatbot's ability to handle complex queries were noted as limiting factors in customer trust and satisfaction. The study highlights the implications of these findings for the future of digital banking in Indonesia, emphasizing the need for improved chatbot integration, stronger data security measures, and enhanced user experience design. The integration of AI in customer service operations holds significant potential for digital banks and the broader financial sector to improve operational efficiency, reduce costs, and meet the evolving expectations of customers.